Increasing Business Survival Rate with Data Integration Business Strategy and Technology Commercialization - Maulana, Danis; Arif, M. Lukman; Akseptori, Ristanti; Novrita Devi, Yesica (Jurnal Entrepreneur dan Entrepreneurship, 2022)
Increasing Business Survival Rate with Data Integration Business Strategy and Technology Commercialization Abstract Technology commercialization is a series of processes from the development and marketing of a technology that is designed to reach a point that can be applied to a production or consumption activity so that it can generate profits. The success or failure of the commercialization of technology-based businesses is influenced by several factors, including the capacity of startups as technology-based entrepreneurs, mentors who accompany, incubation centers that carry out the incubation process, and value of the Technology Readiness Level (TKT) of commercialized technology products. This study aims to explain the increase in startups business survival rates with data integration of business strategies and technology commercialization. This research was conducted with the stages of exploring the problems and conducting a SWOT analysis of East Java startups, analyzing survival rate, making information system prototypes, and analyzing data integration and business strategies. The results showed that Usability Testing received an assessment of 87% consisting of 86% Easy of Use aspect, 88% Easy of Learning aspect, 86% Satisfaction aspect, and 89% on the Usefulness aspect. So information system designed is included very worthy category. The largest percentage of business problems by the HRM (24%) and Operations (24%) therefore need to get attention for solutions. Keywords: survival rate, startup, macroeconomics, Technology Readiness Level, prototype